Mechanical activation of portland cement with ground quartz sand and its effect on the compressive strength of concrete - BARABASH Іvan; KIRSANOV , Mykola (Ways to Improve Construction Efficiency, 2025)
In the production of concrete and reinforced concrete products, Portland cements with finely dispersed mineral additives have become widely used. Ground quartz sands are among the most common mineral additives. Such blended cements can be produced using technologies involving: a) the joint grinding of Portland cement clinker, dihydrate gypsum, and quartz sand; b) the mixing of Portland cement with ground quartz sand dried to a constant mass. To improve the mechanical characteristics of both the cement stone and the resulting concrete, intensive mechanochemical activation of the blended binder in high-speed forced-action mixers has become widely adopted. The experimental results obtained in this article reflect the influence of the mechanochemical activation of Portland cement with the addition of ground quartz sand in the presence of the SP-5 superplasticizer on the compressive strength of concrete at the ages of 3, 7, and 28 days of curing under normal conditions. The activated Portland cement was obtained by high-speed mixing of a highly concentrated suspension of PC I-500 Portland cement with a metered amount of ground quartz sand. The consumption of ground sand varied in the range of 30 to 60% by weight of the blended binder. The block of experimental research was conducted using a D-optimal mathematical plan with the variation of the following independent factors: X₁ – consumption of the blended binder in the range of (370 ± 50) kg/m³; X₂ – consumption of ground quartz sand at (45 ± 15) % by weight of the blended binder; X₃ – consumption of the SP-5 superplasticizing additive at (0.5 ± 0.5) % by weight of the blended binder. Mathematical models indicate that factors X₂ and X₃ have the maximum impact on the strength of concrete at 3, 7, and 28 days of age. An increase in the ground quartz sand content in the blended binder from 30 to 60% causes a decrease in concrete strength for all specified curing periods, while increasing the SP-5 consumption from 0 to 1% provides virtually the same percentage of increase in concrete strength. The combined effect of using mechanochemical activation of Portland cement with ground quartz sand and using SP-5 in an amount of 1.0% contributes to an increase in concrete strength (compared to the control, where mechanical activation is absent) by an average of 25–50%.